New species of Macrobrachium Bate (Decapoda: Caridea: Palaemonidae) from mountainous region Chi Linh (Hai Duong) Northern Vietnam - Thanh, Dang Ngoc (Academia Journal of Biology, 2012)
Macrobrachium chilinense sp. n.   Prawn of moderate size, body length 51-54 mm. Carapace glabrous, without microspinules. Rostrum narrow, straight overeaching Ant I peduncle, just reaching distal end scaphocerite. Rostrum formula: 3 + 7-8/3. Dorsal teeth unequally spaced, usually with wide gaps between 1-3 teeth on carapace. Second pereopods equal in size with body length, left and rigth similar in shape, all segments cylindrical form, covered with microspinules. Merus shorter than carpus (ratio 12/15), carpus scarcely equal in size with palm. Fingers very short, in comparision with palm, (0.3 times), distally armed with seta tuft, both moveable and immoveable fingers with 2 proximal teeth. First pleopod in male with endopod slightly concave at inner margin. Sexual dimorphism showed in smaller second pereopods in female. Eggs dimension d = 1-1.2 mm. Dimensions (male): (mm) tl; 51-54; cl: 15; M; 11-12: C: 14-16; D = 5-6.